Evaluation of new spiral shear reinforcement pattern for reinforced concrete joints subjected to cyclic loading - Azimi, M. (Multi-Science Publishing Co. Ltd, 2016)
Using continuous spiral reinforcements can greatly improve the seismic performance of reinforced concrete columns, in terms of ductility and energy dissipation capacity. The simultaneous incorporation of this method in beams and columns might influence the behaviour of beam-column connections as wide spectrums of brittle failure were observed in this region. A new proposed beam-column connection introduced as 'twisted opposing rectangular spiral' was investigated in this research in both experimental and numerical manners along with comparing its seismic performance with both normal rectangular spiral and conventional shear reinforcement systems. The design of three full-scale beam-column connections was performed according to Eurocode (EC8-04) for high ductility classes, and the quasi-static cyclic loading recommended by American Concrete Institute Building Code (ACI 318-08) was hired to conduct the seismic tests. Finally, the experimental results were validated by numerical results obtained from the finite element analysis of the three specimens. The results revealed improved ultimate lateral resistant, energy dissipation capacity and ductility for the new proposed connection.